PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATA KULIAH KEWIRAUSAHAAN PROGRAM STUDI PENDIDIKAN KESEJAHTERAAN KELUARGA UNIVERSITAS NEGERI PADANG - Karmila, Melsah; Yulastri, Asmar; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims at developing interactive multimedia valid and practical in entrepreneurship courses and analyze the validity and practicalities of multimedia are developed. This research is a development model that IDI consists of three stages: define (determine), develop (development) and Evaluate (ratings). Subjects consisted of 4 validator, 30 students to test the practicalities. The technique of collecting data using questionnaires and analyzed with the formula Aiken's V for validity analysis and descriptive analysis using a percentage formula for analysis practicalities. The results showed that the value of design validation 0.83 with valid category and validation of the contents of 0.83 with a valid category. Test the practicalities of the two lecturers, obtained an average score of 83.85% with a very practical category. Test the practicalities of the students obtained an average score of 83.03% with a very practical category. Based on the above it can be concluded that interactive multimedia is valid and very practical for use as a medium of learning in the Family Welfare Education courses State University of Padang.Keywords: development, multimedia, interactive, entrepreneurship